Syringomyelia: determining risk and protective factors in the conformation of the Cavalier King Charles Spaniel dog - Mitchell, Thomas J (Canine Genet Epidemiol, 2014)
BACKGROUND: Syringomyelia (SM) is a painful neurological condition, prevalent in brachycephalic toy breeds including the Cavalier King Charles Spaniel (CKCS). In these breeds, SM is typically secondary to Chiari-like Malformation (CM). There has been much debate in the scientific and veterinary communities to what extent head shape is indicative of either pathology, especially as certain craniosynostosis syndromes in humans (highly associated with CM) have characteristic facial and cranial morphologies. Elucidating a risk morphology would allow for selection away from these traits and proffer further breeding guidelines for the condition. Dogs were measured in multiple countries by means of a standardised bony landmark measuring protocol and photo analysis by blinded, trained researchers. RESULTS: The results found two significant risk factors in the conformation of the CKCS: extent of brachycephaly and distribution of cranium. The study identified a greater amount of cranium distributed caudally (relative to the amount distributed rostrally) to be significantly protective against syrinx development at the levels of three years of age, five years of age and when comparing a sample of SM clear individuals over the age of five to those affected younger than three years of age. A decreased cephalic index (decreasing brachycephaly) was significantly protective at the latter level. Cephalic index and caudal cranium distribution exhibited a negative, linear relationship. Cephalic index demonstrated a positive linear relationship with the amount of doming of the head. CONCLUSIONS: This study proposes a risk phenotype of brachycephaly with resulting rostrocaudal doming that is more rostrally distributed and hence sloping caudally. The results of this study may allow for selection against risk aspects of conformation in the CKCS in combination with the British Veterinary Association/Kennel Club CM/SM scheme to enable reduction in CM/SM incidence. Further research comparing this external risk phenotype to the internal presentation upon MRI would determine how these features are indicative of syrinx development. Utilising breeds in which CM free individuals are more available may allow for validation of this risk phenotype for CM or determine alternatives.